Gambaran Sarana Sanitasi Lingkungan Pada Rumah Tangga Balita Penderita Stunting Di Puskesmas Rawat Inap Daya Murni Kecamatan Tumijajar Kabupaten Tulang Bawang Barat Tahun 2026 - Inge Ara Della; Karbito Karbito; Tati Baina Gultom (STIKES Columbia Asia Medan, 2026)
Background: Stunting is a chronic nutritional problem that remains a public health concern in Indonesia. One of the factors contributing to stunting is inadequate household environmental sanitation. Poor sanitation can increase the risk of infectious diseases that hinder children’s growth and development. Objective: To describe environmental sanitation facilities in households with stunted children under five in the service area of the Daya Murni Inpatient Health Center, Tumijajar District, West Tulang Bawang Regency, in 2026. Methods: This descriptive study used a total sampling technique involving 19 households with stunted children under five. Data were collected through interviews and observations using a checklist and analyzed using univariate analysis. Results: Most environmental sanitation facilities did not meet health standards, including water supply facilities (73.7%), household latrines (57.9%), solid waste disposal facilities (89.5%), and wastewater disposal facilities (84.2%). Conclusion: Environmental sanitation conditions in households with stunted children under five remained inadequate. Therefore, improvements in basic sanitation facilities and increased community education are needed to support efforts to prevent stunting.